Risk of colorectal and endometrial cancer for carriers of mutations of the hMLH1 and hMSH2 gene: correction for ascertainment - Quehenberger, F (BMJ Group, 2005)
Background: Hereditary non-polyposis colorectal cancer (HNPCC) is caused by germline mutations of mismatch repair genes, usually in hMLH1 or hMSH2. All earlier studies on penetrance except one population based study were conducted in HNPCC families and did not correct for the way in which these families were ascertained. Objective: To obtain estimates of the risk of colorectal cancer (CRC) and endometrial cancer (EC) for carriers of disease causing mutations of the hMSH2 and hMLH1 genes. Methods: Families with known germline mutations of hMLH1 (n = 39) and hMSH2 (n = 45) were extracted from the Dutch HNPCC cancer registry. Ascertainment-corrected maximum likelihood estimation was carried out on a competing risks model for cancer of the colorectum and endometrium. Results: Both loci were analysed jointly as there was no significant difference in risk (p = 0.08). At age 70, colorectal cancer risk for men was 26.7% (95% confidence interval, 12.6% to 51.0%) and for women, 22.4% (10.6% to 43.8%); the risk for endometrial cancer was 31.5% (11.1% to 70.3%). Conclusions: Current estimates of the CRC risk of mutations to the hMLH1 and hMSH2 locus should be replaced by considerably lower risks which account for the selection of the families.